Three-dimensional maxillary and mandibular regional superimposition using cone beam computed tomography: a validation study. Issue 5 (May 2016) - Koerich, L.; Burns, D.; Weissheimer, A.; Claus, J.D.P.
Abstract: This study aimed to validate a novel method for fast regional superimposition of cone beam computed tomography (CBCT) scans. The method can be used with smaller field of view scans, thereby allowing for a lower radiation dose. This retrospective study used two dry skulls and secondary data from 15 patients who had more than one scan taken using the same machine. Two observers tested two types of regional voxel-based superimposition: maxillary and mandibular. The registration took 10–15 s. Three-dimensional surface models of the maxillas and mandibles were generated via standardized threshold segmentation, and the accuracy and reproducibility of the superimpositions were assessed using the iterative closest point technique to measure the root mean square (RMS) distance between the images. Five areas were measured and a RMS ≤ 0.25 was considered successful. Descriptive statistics and the intra-class correlation coefficient (ICC) were used to compare the intra-observer measurement reproducibility. The ICC was ≥0.980 for all of the variables and the highest RMS found was 0.241. The inter-observer reproducibility was assessed case by case and was perfect (RMS 0) for 68% (23 out of 34) of the superimpositions done and not clinically significant (RMS ≤ 0.25) for the other 32%. The method is fast, accurate, and reproducible and is an alternative to cranial base superimposition.